2004
DOI: 10.1002/mana.200310194
|View full text |Cite
|
Sign up to set email alerts
|

Atomic decomposition for the vorticity of a viscous flow in the whole space

Abstract: We show that the vorticity of a viscous flow in R 3 admits an atomic decomposition of the form ω(, with localized and oscillating building blocks ω k , if such a property is satisfied at the beginning of the evolution. We also study the long time behavior of an isolated coherent structure and the special behavior of flows with highly oscillating vorticities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Note that the decay profiles of ω and Ω are the same which can be obtained for the solutions of the homogeneous heat equations e t∆ ω 0 (x) and e t∆ Ω 0 (x), respectively. We refer to [6] for a proof of (13) (the proof of (11) is identical). The decay of the vorticity in the L p -norm are formally a consequence of (11) and (13), respectively if d = 2 or 3.…”
Section: Decay Of the Velocity Field And The Vorticitymentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the decay profiles of ω and Ω are the same which can be obtained for the solutions of the homogeneous heat equations e t∆ ω 0 (x) and e t∆ Ω 0 (x), respectively. We refer to [6] for a proof of (13) (the proof of (11) is identical). The decay of the vorticity in the L p -norm are formally a consequence of (11) and (13), respectively if d = 2 or 3.…”
Section: Decay Of the Velocity Field And The Vorticitymentioning
confidence: 99%
“…The decay of the vorticity in the L p -norm are formally a consequence of (11) and (13), respectively if d = 2 or 3. Estimates (12) and (14), however, can be proved with straightforward adaptations of the arguments of [11]- [6], or [16]- [17] (see also [8]).…”
Section: Decay Of the Velocity Field And The Vorticitymentioning
confidence: 99%
See 1 more Smart Citation
“…where (x m ) is a sequence of points in R n and u m (·, t) are L ∞ functions decaying at infinity as |x| −(n+1) , holds true (see [1]). Expanding u(·, t) ∈ p>0Ḃ n/p,p p (R n ) by means of dilated-translated Poisson kernels (which have the "right" decay rate) is therefore more meaningful, from the physical point of view, than expressing the velocity field as a series of too localized functions, such as gaussians or wavelets.…”
Section: Lorenzo Brandolesementioning
confidence: 99%
“…the motion of a viscous incompressible fluid filling the whole space R n and not submitted to the action of external forces. If u(x, t) denotes the velocity of a fluid particle at time t, then under suitable assumptions on the vorticity of the flow, it can be shown that u(·, t) ∈ p>0Ḃ n/p,p p (R n ), uniformly in time (see [1]). For an application of sparse wavelet expansions to numerical simulations of flows we refer to [15].…”
Section: Lorenzo Brandolesementioning
confidence: 99%